Direct PCR of Small Genomic DNA Fragments from Serum. (November 1997) - Sandford, Andrew J.; Paré, Peter D.
A simple and rapid method is described where human genomic DNA suitable for PCR was prepared from serum by microwave irradiation. We were able to reproducibly amplify single-copy gene sequences up to 442 bp from small quantities of serum without the need for DNA extraction. Genotyping results obtained from serum samples were shown to be identical to those derived from purified DNA from the same individuals.